The Mitotic Index of Cajanus cajan from Kisar Island, in the Southwest of Maluku - Kristin Sangur; Alwi Smith; Meike Tomasoa (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2021)
The mitotic index of the roots of pigeon pea can be the basis for determining the growth of pigeon pea. The purpose of this research was to determine the time of root cell division, to observe the mitotic phases, and to determine the mitotic index of pigeon pea root cells. The preparation of the pigeon pea was carried out for 4 days to grow the roots. The roots were cut off at 08.00, 08.15, and 08.30 WIT (Eastern Indonesian Time). The roots were cut 0.5-1cm. Carnoy’s solution was used as the fixative solution using the Squash technique. The prepared roots were then observed using an Olympus cx-22 microscope and an OptiLab camera with a magnification of 100x40. The data were descriptively analyzed to describe the images of mitotic phases and the mitotic index presentation in the root cells of pigeon pea. The results of this research showed that the cell division of the pigeon pea roots began at 08.00 WIT, which was marked by the presence of a lot of prophase. The next phases that appeared were prometaphase, metaphase, and anaphase which occurred from 08.15 to 08.30 with different numbers. The highest mitotic index occurred at 08.15, when most of the root cells underwent metaphase. This study succeeded in revealing that the optimum time for pigeon pea root cell division is 08.15 WIT. In the future, this research can help pigeon pea farmers in Southwest of Maluku to carry out vegetative reproduction which is closely related to this mitotic study.